Padlina i sępy. Czy logion Q 17,37 jest biblijnym cytatem (illud dictum), przysłowiem (proverbium) czy znakiem (signum)? Analiza egzegetyczno-teologiczna - Zawadzki, Arnold (The Biblical Annals, 2020)
The article proposes a detailed syntactic and semantic analysis of Mt 24:28 and Lk 17:37c for the purpose of hypothetical reconstructing of the original Semitic (Hebrew and Aramaic) form of the logion Q 17:37. Then it is offered the comparison between the three different hermeneutic opportunities in its understanding within the canonical context, as either biblical quotation/paraphrase (Job 39,30) or proverb or sign. This comparison helps to understand that Q 17:37 fits very well to its literary and theological context from these three points of view. It shows therefore a very great semantic flexibility and makes it difficult to establish its original meaning in the Document Q. However, the author of the article argues that the Semitic phrase Q 17,37 with a very high probability functioned both in the Document Q and in the canonical context as a quotation/paraphrase of Job 39:30 or as a sign (in the same way as the fig sign in Mt 24.32-33; Lc 21.29-31) rather than as a proverb. The article therefore undermines the classical view that would be consolidated in the modern exegesis on Mt 24:28; Lk 17,37c.